EFFECT OF SEED TUBER DESPROUTING ON POTATO PRODUCTION IN KUFRI GIRIRAJ - Sharma, Ashwani Kumar; Singh, Sarjeet (Potato Journal, 2013)
Potato cultivars are known to vary in their response to desprouting. Due to the lack of information on desprouting behaviour of potato cv. Kufri Giriraj, a study was conducted to find out the desprouting behaviour with different sizes of seed tubers (20, 40, 60 g), under north-western hill conditions at Central Potato Research Station, Kufri, Shimla. The results revealed no difference in the sprouting pattern between non-desprouted and once or twice desprouted seed tubers. The total as well as seed size (20-80 g), number of tubers and yield were not influenced significantly with one or two desproutings. Increasing size of the seed tuber from 20 to 60 g resulted in a significant increase in the tuber number and yield.